Electrical tuning effect for Schottky barrier and hot-electron harvest in a plasmonic Au/TiO2 nanostructure - Zhiguang Sun (Nature Portfolio, 2021)
Abstract Schottky barrier controls the transfer of hot carriers between contacted metal and semiconductor, and decides the performance of plasmonic metal–semiconductor devices in many applications. It is immensely valuable to actively tune the Schottky barrier. In this work, electrical tuning of Schottky barrier in an Au-nanodisk/TiO2-film structure was demonstrated using a simple three-electrode electrochemical cell. Photocurrents excited at different wavelength significantly increase as the applied bias voltage increases. Analyzing and fitting of experimental results indicate that the photocurrent is mainly affected by the bias tuning position of Schottky barrier maximum, which shifts to metal–semiconductor interface as applied voltage increases, and enhances the collection efficiency of the barrier for plasmonic hot electrons. The conduction band curvature of 0.13 eV was simultaneously obtained from the fitting. This work provides a new strategy for facile tuning of Schottky barrier and hot-electron transfer across the barrier.